Systematic review of 3D printing in spinal surgery: the current state of play - Wilcox, Ben; Mobbs, Ralph J.; Wu, Ai-Min; Phan, Kevin (Journal of Spine Surgery, 2017)
Three-dimensional printing (3DP), also known as “Additive Manufacturing”, is a rapidly growing industry, particularly in the area of spinal surgery. Given the complex anatomy of the spine and delicate nature of surrounding structures, 3DP has the potential to aid surgical planning and procedural accuracy. We perform a systematic review of current literature on the applications of 3DP in spinal surgery. Six electronic databases were searched for original published studies reporting cases or outcomes for 3DP surgical models, guides or implants for spinal surgery. The findings of these studies were synthesized and summarized. These searches returned a combined 2,411 articles. Of these, 54 were included in this review. 3DP is currently used for surgical planning, intra-operative surgical guides, customised prostheses as well as “Off-the-Shelf” implants. The technology has the potential for enhanced implant properties, as well as decreased surgical time and better patient outcomes. The majority of the data thus far is from low-quality studies with inherent biases linked with the excitement of a new field. As the body of literature continues to expand, larger scale studies to evaluate advantages and disadvantages, and longer-term follow up will enhance our knowledge of the effect 3DP has in spinal surgery. In addition, issues such as financial impact, time to design and print, materials selection and bio-printing will evolve as this rapidly expanding field matures.